1998
DOI: 10.1098/rspb.1998.0515
|View full text |Cite
|
Sign up to set email alerts
|

Should advertising parental care be honest?

Abstract: Species with paternal care show less exaggerated sexual ornamentation than those in which males do not care, although direct bene¢ts from paternal care can vastly exceed the indirect bene¢ts of mate choice. Whether condition-dependent handicaps can signal parenting ability is controversial. The good-parent process predicts the evolution of honest signals of parental investment, whereas the di¡erential-allocation model suggests a trade-o¡ between the attractiveness of a mate and his care-provisioning. I show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
154
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(157 citation statements)
references
References 73 publications
1
154
2
Order By: Relevance
“…Kokko [61] presents an instructive model of parental care and attractiveness. Males differ in quality and each allocates resources to advertising to females, care and self-maintenance in the way that maximizes fitness.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kokko [61] presents an instructive model of parental care and attractiveness. Males differ in quality and each allocates resources to advertising to females, care and self-maintenance in the way that maximizes fitness.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although Kokko's analysis [61] is a major contribution to our understanding of the relationships between attractiveness and effort, it has some limitations in terms of the interactions that we have identified as being required for a fully consistent model. In particular, the interaction between the male and the female is not considered, so the model cannot predict how the parental investment of a female depends on the attractiveness of her mate.…”
Section: Future Directionsmentioning
confidence: 99%
“…This could lead to some individuals cheating if they invest proportionally more in present signalling and less in future signalling than others (Kokko 1998). This might be the case when individuals within a population differ in their future reproductive value.…”
Section:  2000 the Association For The Study Of Animal Behaviourmentioning
confidence: 99%
“…Work in species with male care has focused on the benefits to females of choosing good fathers and the trade-off between offspring care and male survival (Kraak & Weissing 1996;Kraak et al 1999). A recent model of male advertisement of parental care (Kokko 1998) showed that whether a species fits the good-parent hypothesis or the differential-allocation hypothesis depends on a male's marginal gains from multiple matings. This model was intended to apply generally to species where males might provide care, yet allows males to have current reproductive success while providing no care, which makes it inapplicable to species where some male care is required for offspring survival.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical models of honest advertisement of care are also often based on biparental systems of care (Price et al 1993;Westneat & Sargent 1996;Kokko 1998;Kokko et al 2002), where females that choose a male that advertises dishonestly are able to compensate for his decreased level of care by increasing their own level of parental care. This focus on biparental and female-only care systems has resulted in a gap in our understanding of honest advertisement.…”
Section: Introductionmentioning
confidence: 99%